2022
DOI: 10.3389/fimmu.2022.886611
|View full text |Cite
|
Sign up to set email alerts
|

Priming With Rhinovirus Protects Mice Against a Lethal Pulmonary Coronavirus Infection

Abstract: Rhinoviruses (RV) have been shown to inhibit subsequent infection by heterologous respiratory viruses, including influenza viruses and severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). To better understand the mechanisms whereby RV protects against pulmonary coronavirus infection, we used a native murine virus, mouse hepatitis virus strain 1 (MHV-1), that causes severe disease in the lungs of infected mice. We found that priming of the respiratory tract with RV completely prevented mortality and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Such challenges also apply to in vivo studies using animal models. For example, a mouse model study showed that coinfection with IAV and HRV caused milder influenza but did not reduce IAV shedding [8], whereas coinfection with IAV and mouse hepatitis virus strain 1, a murine coronavirus, attenuated disease presentation and reduced IAV replication [7,8], and this was associated with IFN upregulation. In contrast, other studies that investigated in vivo coinfections of IAV and SARS-CoV-2 showed that disease severity was increased in coinfections [34][35][36] and SARS-CoV-2 replication was reduced [34,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such challenges also apply to in vivo studies using animal models. For example, a mouse model study showed that coinfection with IAV and HRV caused milder influenza but did not reduce IAV shedding [8], whereas coinfection with IAV and mouse hepatitis virus strain 1, a murine coronavirus, attenuated disease presentation and reduced IAV replication [7,8], and this was associated with IFN upregulation. In contrast, other studies that investigated in vivo coinfections of IAV and SARS-CoV-2 showed that disease severity was increased in coinfections [34][35][36] and SARS-CoV-2 replication was reduced [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies using air-liquid interface (ALI) cultures of respiratory epithelium support this hypothesis as they showed that some viruses trigger an interferon (IFN)-mediated response that can block a secondary viral infection [2][3][4]. Experimental coinfections using animal models supported the occurrence of virus-virus interactions in vivo [5][6][7][8].…”
mentioning
confidence: 96%
“…Investigations have delved into a clinical syndrome exhibiting similarities to severe acute respiratory syndrome (SARS) in mice infected with murine hepatitis virus-1 (MHV-1). This syndrome is distinguished by a markedly high mortality rate [ 8 , 9 , 10 , 11 , 12 , 13 ]. These mice exhibit pronounced lung injury with mortality rates ranging from 40% to 60% between days 7 and 12 post-infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One demonstrated mechanism of interference among respiratory viruses is induction of the interferon response, a broad antiviral defense mechanism that is induced by most respiratory viruses, and also suppresses replication of most viruses[5-8]. Within the airway epithelium, the replicating viral genome is the initiating trigger of the interferon response[9].…”
Section: Introductionmentioning
confidence: 99%